Thursday

July 2, 2015

July 2, 2015

Posted by **Katy** on Monday, May 31, 2010 at 7:43pm.

I'm stuck on this problem because I'm getting thrown off on how to factor this. Here's my work so far:

-{[(dy/dx)y + y]sin xy} = 4x - 3(dy/dx)

-{[(dy/dx)y + y]sinxy} + 3(dy/dx) = 4x

...now what?

Thx

- Calculus (repost) -
**Damon**, Monday, May 31, 2010 at 9:12pmfactor out dy/dx which is what you want

dy/dx [ 3 -y sinxy] = [ 4 x + y sin xy ]

so

dy/dx =[ 4 x + y sin xy ] / [ 3 -y sinxy]

- Calculus (repost) -
**MathMate**, Monday, May 31, 2010 at 9:29pmThere is a minor correction to the original differentiation:

-{[(dy/dx)**x**+ y]sin xy} = 4x - 3(dy/dx)